Edukasi Mengenai Dampak Kekerasan Pada Ibu Dan Anak Di UPT Puskesmas Kampung Sawah Bandar Lampung - Linawati Novikasari; Aryanti Wardiyah; Setiawati Setiawati; Dewi Kusumaningsih; Eka Yudha Chrisanto; Marlina Agustina; Dina Martiani; Refsi Erpiyana; Alisah Rahmah Hidayah; Asep Rahmad Hidayat; Imanda Sastria; Sastria Handayani (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
Violence against children and women at home and in the workplace is a serious social problem, but there has been little response from society and law enforcement. The National Child Protection Commission (KPAI, 2018) received complaints related to cases of physical violence and victimization of children as much as 72%, followed by psychological violence at 9%, economic violence or bullying/intimidation at 4%, and sexual violence at 2%. The National Children's Commission also reported that the majority of perpetrators of violence against children were parents, 44% of whom were biological mothers, 22% mothers and stepfathers, 18% biological fathers, and 8% caregivers. The aim of this activity is to increase respondents' knowledge regarding the impact of violence on mothers and children. Socialization methods in the form of lectures and questions and answers are used in this activity. It was found that respondents were very enthusiastic about listening to the material presented by the presenters. The conclusion from this activity is that violence against mothers and children must be opposed to prevent the impact that will occur on children.